Saturation-Induced Instability and Its Avoidance in Adaptive Control of Hard Disk Drives - Perez-Arancibia, N.O.; Tsu-Chin Tsao; Gibson, J.S. (IEEE transactions on control systems technology, 2010)
This paper presents an investigation of the design and implementation of minimum-variance adaptive controllers for computer hard disk drive (HDD) read-write track following. A common characteristic of minimum-variance controllers, adaptive or not, is that they rely on prediction filters with large high-frequency gains to predict broadband disturbances, and this often produces control-signal saturation and eventual loss of stability. Two methods are introduced here to address this issue. The first method, suitable for online adaptive control, uses frequency weighting to constrain the high-frequency gain of the prediction filter. The second method, suitable for tuning fixed-gain controllers, employs an adaptive scheme iteratively over a finite duration. Both methods were implemented on a commercial hard disk drive, and experimental results demonstrate their effectiveness.